Māori oral traditions record and convey indigenous knowledge of marine and freshwater resources. Issue 4 (2nd October 2018) - Whaanga, Hēmi; Wehi, Priscilla; Cox, Murray; Roa, Tom; Kusabs, Ian
ABSTRACT: Whakataukī are part of a strongly developed Māori oral tradition that conveys critical information about aspects of life, society and tribal memory, including ecological knowledge. Such codified knowledge depends on language use and structure as a key mechanism for cultural transmission. Additionally, many meanings may not be apparent without knowing the historical, cultural and linguistic context from which the whakataukī originated. We examined a primary dataset of c. 3500 versions of whakataukī, drawn from collections published after European arrival c. 200 years ago, to determine how marine and freshwater principles, practices and knowledge bases have developed in response to changing environmental and societal contexts in Aotearoa. We present information on marine and freshwater resources contained in whakataukī to shed light on the connections between humans and their environment that transcend prosaic uses and enlighten deeper social and behavioural engagement with the surrounding environment. Understanding past engagement can help shape future marine and freshwater relationships in Aotearoa.